Pathogen–nematode interaction: Nitrogen supply of Listeria monocytogenes during growth in Caenorhabditis elegans. Issue 1 (21st December 2015) - Kern, Tanja; Kutzner, Erika; Eisenreich, Wolfgang; Fuchs, Thilo M.
Summary: L isteria monocytogenes is a Gram‐positive facultatively intracellular human pathogen. Due to its saprophytic lifestyle, L . monocytogenes is assumed to infect and proliferate within soil organisms such as C aenorhabditis elegans . However, little is known about the nutrient usages and metabolite fluxes in this bacterium–nematode interaction. Here, we established a nematode colonization model for L . monocytogenes and a method for the efficient separation of the pathogen from the nematodal gut. Following 15 N labelling of C . elegans and gas chromatography–mass spectrometry‐based 15 N isotopologue analysis, we detected a high basal metabolic rate of the nematode, and observed a significant metabolic flux from nitrogenous compounds of the nematode to listerial proteins during proliferation of the pathogen in the worm's intestine. For comparison, we also measured the N fluxes from the gut content into listerial proteins using completely 15 N‐labelled E scherichia coli OP50 as food for C . elegans . In both settings, L . monocytogenes prefers the direct incorporation of histidine, arginine and lysine over their de novo biosynthesis. Our data suggest that colonization of nematodes is a strategy of L . monocytogenes to increase its access to N‐rich nutrients.